let D, E be non empty set ; :: thesis: for d being Element of D
for i being natural Number
for h being Function of D,E
for T being Tuple of i,D
for F being BinOp of D
for H being BinOp of E st ( for d1, d2 being Element of D holds h . (F . (d1,d2)) = H . ((h . d1),(h . d2)) ) holds
h * (F [:] (T,d)) = H [:] ((h * T),(h . d))

let d be Element of D; :: thesis: for i being natural Number
for h being Function of D,E
for T being Tuple of i,D
for F being BinOp of D
for H being BinOp of E st ( for d1, d2 being Element of D holds h . (F . (d1,d2)) = H . ((h . d1),(h . d2)) ) holds
h * (F [:] (T,d)) = H [:] ((h * T),(h . d))

let i be natural Number ; :: thesis: for h being Function of D,E
for T being Tuple of i,D
for F being BinOp of D
for H being BinOp of E st ( for d1, d2 being Element of D holds h . (F . (d1,d2)) = H . ((h . d1),(h . d2)) ) holds
h * (F [:] (T,d)) = H [:] ((h * T),(h . d))

let h be Function of D,E; :: thesis: for T being Tuple of i,D
for F being BinOp of D
for H being BinOp of E st ( for d1, d2 being Element of D holds h . (F . (d1,d2)) = H . ((h . d1),(h . d2)) ) holds
h * (F [:] (T,d)) = H [:] ((h * T),(h . d))

let T be Tuple of i,D; :: thesis: for F being BinOp of D
for H being BinOp of E st ( for d1, d2 being Element of D holds h . (F . (d1,d2)) = H . ((h . d1),(h . d2)) ) holds
h * (F [:] (T,d)) = H [:] ((h * T),(h . d))

let F be BinOp of D; :: thesis: for H being BinOp of E st ( for d1, d2 being Element of D holds h . (F . (d1,d2)) = H . ((h . d1),(h . d2)) ) holds
h * (F [:] (T,d)) = H [:] ((h * T),(h . d))

let H be BinOp of E; :: thesis: ( ( for d1, d2 being Element of D holds h . (F . (d1,d2)) = H . ((h . d1),(h . d2)) ) implies h * (F [:] (T,d)) = H [:] ((h * T),(h . d)) )
assume A1: for d1, d2 being Element of D holds h . (F . (d1,d2)) = H . ((h . d1),(h . d2)) ; :: thesis: h * (F [:] (T,d)) = H [:] ((h * T),(h . d))
per cases ( i = 0 or i <> 0 ) ;
suppose A2: i = 0 ; :: thesis: h * (F [:] (T,d)) = H [:] ((h * T),(h . d))
then F [:] (T,d) = <*> D by Lm3;
then A3: h * (F [:] (T,d)) = <*> E ;
h * T = <*> E by A2;
hence h * (F [:] (T,d)) = H [:] ((h * T),(h . d)) by ; :: thesis: verum
end;
suppose i <> 0 ; :: thesis: h * (F [:] (T,d)) = H [:] ((h * T),(h . d))
then reconsider C = Seg i as non empty set ;
T is Function of C,D by Lm4;
hence h * (F [:] (T,d)) = H [:] ((h * T),(h . d)) by ; :: thesis: verum
end;
end;